ঢাকার স্মৃতি ১ / ১ - মামুন, মুনতাসীর 1951-; Stock, A. G. (Amy Geraldine), 1902-1988. (Ḍhākā : ঢাকা Māolā Brādārsa, মাওলা ব্রাদার্স, 2001)
Collection of autobiographical reminiscences of 18th-19th and early 20th century social history of Dhaka, Bangladesh, written by various Bengali writers.
Vol. 2: translation of Memoirs of Dacca University, 1947-1951 / A.G. Stock. Dacca : Green Book House, 1973.
Includes bibliographical references.
In Bengali.
Keywords: Dhaka (Bangladesh) -- History; Dhaka (Bangladesh) -- Biography